A hybrid technique employed for efficiency improvement of tandem perovskite solar cell. (7th August 2022) - Subha, T. D.; Arunachalaperumal, C.; Subash, T. D.; Jeepa, K. J.
Abstract: A hybrid approach is proposed for the influence of contact electrode and light power on the performance of tandem perovskite sun mobileular. The proposed hybrid method is the joint performance of human urbanization algorithm (HUA) and balancing composite motion optimization (BCMO); hence, it is known as HUA‐BCMO approach. The goal of the proposed system is (a) to analyze the layer composition of tandem perovskite solar mobileular, (b) to analyze the overall performance of formamidinium tin based totally perovskite sun mobileular, (c) to model an efficient hybrid sun mobileular, and (d) to examine the overall performance of the proposed sun mobileular. The impact of the absorber layer can be investigated and optimized the gadgets with the assist of HUA‐BCMO approach. Moreover, in this paper analyzed the impacts of various materials like electron transport layer, hole transport layer and the effect of back metal contact, absorber layer etc.  Molecular dynamic examine can be discovered that the thermal properties of perovskite layers can be favorable to the sun mobileular efficiency and overall performance. Moreover, the impact of temperature variation on sun mobileular is analyzed and overall efficiency can be explored. It is found that low defect density to obtain high device performance. The overall performance of the proposed hybrid approach can be applied on MATLAB platform and as compared with current techniques. Abstract : A hybrid HUA‐BCMO approach is proposed for the influence of contact electrode and light power on the performance of tandem perovskite solar PV cell. The overall performance is applied in the MATLAB platform. The impact of temperature version on sun mobileular overall performance and effect of defect density of absorber layer can be explored. It is found that low defect density to achieve high device performance.